AVALIAÇÃO FÍSICO-QUÍMICA E MICROBIOLÓGICA DO CAMARÃO Litopenaeus vannamei SUBMETIDO À DEFUMAÇÃO LÍQUIDA EM DIFERENTES TEMPERATURAS E TEMPOS DE PROCESSAMENTO: Physicochemical and microbiological evaluation of shrimp Litopenaeus vannamei submitted to liquid smoking at different temperatures and processing time - Campagnoli de Oliveira Filho, Paulo Roberto; da Silva, Chirley Matilde; Estolano Macedo, Indira Maria (Arquivos de Ciências do Mar, 2022)
One way to preserve shrimp is the use of liquid smoking. This study aimed to evaluate physicochemical and microbiological aspects of shrimp subjected to liquid smoking by testing different times and temperature. Shrimp were oven smoked using liquid smoke with the following treatments: A - 80°C/5h, B - 85°C/4h, C - 90°C/3h. Yield, shrinkage, color, texture, water holding capacity, water activity, moisture and microbiological analyses were performed. The liquid smoking of shrimp from Treatment A caused lower yield, higher percentage of shrinkage, higher water holding capacity, higher hardness and lower percentage of moisture and water activity. In the shrimp from Treatment C, there was higher yield, lower percentage shrinkage, lower water holding capacity, lower hardness, and higher percentage of moisture and water activity. In the microbiological analyses, the results were in accordance with the Brazilian legislation. It can be concluded that the liquid smoking of shrimp of treatment C shows itself to be more suitable, having a great potential for production and commercialization. Keywords: smoked fish, conservation, liquid smoke, crustacean.